Pengaruh Pijat Endorphin Terhadap Penurunan Intensitas Nyeri Persalinan Di BPM Sagita Darma Sari Palembang Tahun 2023 - Sartika Ratna Sari; Yuyun Triani (Pusat Riset dan Inovasi Nasional, 2023)
Background: Childbirth is a series of events when a baby is released from the mother's womb, followed by the expulsion of the placenta and fetal membranes from the mother's body. The main problem that is usually complained of by labor patients in labor during the first active phase is that pain causes the mother to feel stressed and excessively worried. Respiration and pulse will also increase thereby disrupting the supply of fetal needs from the placenta. The simple way that can be done to reduce labor pain is to give endorphins massage. Objective: Knowing the analysis of differences in pain intensity in the active phase of labor in the first stage of labor before endorphin massage and after endorphin massage. Method: This study used a quasy experimental design. This type of research is pre-experimental design with one group pret test-post test design. Results: The results of the study obtained by the researchers were 20 respondents during the active phase of the first active phase of brenatal mothers who experienced severe pain with a scale of 7-9 and very severe 10 as measured by a numeric rating scale. Before doing the endorphin massage, it was found that those who experienced pain on average had a minimum of 5 and a maximum of 10 after the endorphin massage had an average minimum of 4 pain and a maximum of 9. Conclusion: There is a difference in the decrease in pain intensity in labor in labor during the 1st active phase before and after being given endorphine massage treatment.